Evaluation of different mango (Mangifera indica) varieties for high density orchard in lateritic zone of eastern India - MANDAL, GOUTAM; THOKCHOM, ROCKY (The Indian Journal of Agricultural Sciences, 2018)
The present experiment was conducted under the semi-arid subtropical red lateritic zone of eastern India in West Bengal with seven years old popular mango (Mangifera indica L.) varieties grown at Horticulture Research Farm of Department of Horticulture and Postharvest Technology, Institute of Agriculture, Visva-Bharati, Sriniketan, West Bengal, India during 2015 and 2016. The varieties were evaluated for various morphological characters, yield and physicochemical quality of fruits. The results revealed that Kohinoor exhibited maximum tree volume (41.99 m3), fruit yield (21.03 kg/tree) and fruit weight (253.33 g/fruit). Whereas, Kohitoor exhibited maximum TSS (20.07 oB), TSS/acid ratio (100.35) and ascorbic acid (43.17 mg/100g) content of the fruits. Acidity content was found lowest (0.17%) in Gulab Khas. Regarding morphological characters, yield and physicochemical quality of fruits, the varieties Kohinoor, Kohitoor, Inayat Pasand are superior in quality and stand to promise for the small family farming orchard in the red lateritic zone of eastern India.